Solid-state battery pole piece with ultrathin solid electrolyte coating as well as preparation method and application of solid-state battery pole piece

By applying an ultra-thin solid electrolyte layer on the surface of the lithium battery electrode sheet, the problems of degraded electrochemical performance and increased safety risks in the prior art are solved, and higher battery performance and safety are achieved.

CN119673949APending Publication Date: 2025-03-21上海科源固能新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913560.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to apply an ultra-thin and dense solid electrolyte layer on the surface of the lithium battery electrode sheet, resulting in a decrease in electrochemical performance and an increased safety risk.

Method used

After preparing solid electrolyte slurry, refining the sand mill and stirring it with the binder PVDF, the application is performed using a microconcave coating machine and heating rolling is carried out to achieve the purpose of ultra-thin solid electrolyte coating.

Benefits of technology

The density of the ultra-thin solid electrolyte coating on the surface of the electrode sheet is achieved, and safety is retained, while improving the electrochemical performance and rate performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673949A_ABST
    Figure CN119673949A_ABST
Patent Text Reader

Abstract

The invention relates to a solid-state battery pole piece with an ultrathin solid-state electrolyte coating as well as a preparation method and application of the solid-state battery pole piece. Firstly, solid electrolyte slurry is prepared; the dispersed solid electrolyte slurry is refined by a sand mill, and refined solid electrolyte slurry with the particle size being 200 nm or below is obtained; adding a binder PVDF (Polyvinylidene Fluoride) into the refined solid electrolyte slurry, and stirring; coating the solid electrolyte slurry on the surface of a pole piece by using a micro gravure coating machine, and drying to obtain a battery pole piece of which the surface is coated with the solid electrolyte; and heating and rolling the battery pole piece of which the surface is coated with the solid electrolyte to obtain the solid-state battery pole piece with the ultrathin solid electrolyte coating. Compared with the prior art, the invention provides the ultrathin coating method for the surface of the pole piece of the solid-state battery, so that the safety of the solid-state electrolyte coating layer is kept, the negative influence of the solid-state electrolyte coating layer on the electrochemical performance of the lithium battery is eliminated, and even the rate capability of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state battery materials, and in particular relates to a solid-state battery pole piece with an ultra-thin solid electrolyte coating, and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium battery technology, the energy density of batteries is increasingly required, but the higher the energy density of lithium batteries, the greater the safety risks of lithium batteries. The emergence of solid-state electrolyte technology has greatly weakened the safety risks of high energy density, but it has also reduced some of the electrochemical properties of lithium batteries, especially the technology of coating solid-state electrolytes on the surface of electrode sheets. This technology generally coats a 10um to 40um solid electrolyte layer on the surface of the electrode sheet, which can effectively prevent the possibility of contact between the positive and negative electrodes, but it also greatly increases the impedance of the battery, resulting in a decrease in capacity and poor rate performance. How to reduce or even eliminate the impact of solid-state electrolyte technology on the electrochemical performance of lithium batteries on the surface of the electrode sheet is the most critical issue for the mass production of this technology. Summary of the invention

[0003] At present, a key difficulty in applying the technology of coating the surface of electrode sheets with solid electrolytes is how to make the solid electrolyte coating on the surface of the electrode sheets ultra-thin and dense. The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a solid-state battery electrode sheet with an ultra-thin solid electrolyte coating and its preparation method and application.

[0004] The present invention provides a method for preparing an ultra-thin coating on the surface of a solid-state battery pole piece. The coating layer thickness can reach 1.5um, which not only retains the safety of the solid electrolyte coating layer, but also eliminates the negative impact of the solid electrolyte coating layer on the electrochemical performance of the lithium battery, and even improves the rate performance of the lithium battery.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] The present invention first provides a method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating, comprising the following steps:

[0007] 1) preparing a solid electrolyte slurry;

[0008] 2) refining the dispersed solid electrolyte slurry with a sand mill to obtain a refined solid electrolyte slurry with particles of less than 200 nm;

[0009] 3) adding the refined solid electrolyte slurry to the binder PVDF and stirring;

[0010] 4) applying the solid electrolyte slurry prepared in step 3) on the surface of the electrode using a micro-concave coating machine, and drying to obtain a battery electrode with a surface coated with a solid electrolyte;

[0011] 5) The battery pole piece with the solid electrolyte coated on the surface is subjected to a heating and rolling process to obtain a solid-state battery pole piece with an ultra-thin solid electrolyte coating.

[0012] In one embodiment of the present invention, the solid content of the solid electrolyte slurry in step 1) is 5-40 wt %, preferably, the solid content is 15 wt %.

[0013] In one embodiment of the present invention, the solid electrolyte material of the solid electrolyte slurry in step 1) is an oxide solid electrolyte, a sulfide solid electrolyte or a halide solid electrolyte, selected from one or a combination of LATP, LLZO, LLZTO, LLTO, LAGP, LSPC, LGPS, LIC or LYC. Preferably, the solid electrolyte material of the solid electrolyte slurry in step 1) is LATP.

[0014] In one embodiment of the present invention, the solvent of the solid electrolyte slurry in step 1) is N-methyl-2-pyrrolidone.

[0015] In one embodiment of the present invention, a dispersant is added to the solid electrolyte slurry in step 1), and the amount of the dispersant added is 0.1 wt% to 1 wt%, preferably 0.2 wt%.

[0016] In one embodiment of the present invention, a dispersant is added to the solid electrolyte slurry in step 1), and the dispersant is selected from one or a combination of polyvinyl pyrrolidone, herring oil or PAM, preferably polyvinyl pyrrolidone.

[0017] In one embodiment of the present invention, when preparing the solid electrolyte slurry in step 1), the solid electrolyte material, solvent and dispersant are stirred and dispersed using a stirrer, and the linear speed of stirring the solid electrolyte slurry is 1 to 6 m / s.

[0018] Preferably, when preparing the solid electrolyte slurry in step 1), the linear speed of the stirring and dispersing using a stirrer is 4 m / s.

[0019] In one embodiment of the present invention, in step 2), the feed rate of the sand mill is controlled at 1-30 L / min, the linear speed of the sand mill is controlled at 20-90 m / min, the filling rate of the sand mill is controlled at 25-65%, and the grinding media used in the sand mill is selected from one or a combination of zirconium oxide beads, glass beads, steel beads or zirconium silicate beads.

[0020] In one embodiment of the present invention, in step 2), preferably, the feed rate of the sand mill is controlled to 5 L / min, the linear speed of the sand mill is controlled to 50 m / min, the filling rate of the sand mill is controlled to 48%, and the grinding medium used in the sand mill is selected from zirconia beads.

[0021] In one embodiment of the present invention, in step 3), the mass ratio of PVDF to solid electrolyte is 6:94 to 25:75; in step 3), a disperser is used for stirring, the stirring line speed of the disperser is 1 to 6 m / s, and the stirring time of the disperser is 1 to 12 h.

[0022] In one embodiment of the present invention, preferably, in step 3), the mass ratio of PVDF to solid electrolyte is 13:87, and in step 3), a disperser is used for stirring, the stirring line speed of the disperser is 4 m / s, and the stirring time of the disperser is 6 h.

[0023] In one embodiment of the present invention, in step 4), the coating speed of the dimple coater is 5 to 60 mm / s, and the dimple mesh number is 50 to 300 meshes. Preferably, the coating speed of the dimple coater is 15 mm / s, and the dimple mesh number is 250 meshes.

[0024] In one embodiment of the present invention, in step 4), an oven is used for drying at a temperature of 90-120° C. Preferably, the selected oven is a three-stage oven with a length of 7 m and an oven temperature of 95, 105, 100° C.

[0025] In one embodiment of the present invention, in step 5), when the heating roller pressing treatment is performed, the pressure of the roller press is 10-80t, and the temperature of the heating roller is 60-110° C. Preferably, in step 5), when the heating roller pressing treatment is performed, the pressure of the roller press is 40t, and the temperature of the heating roller is 90° C.

[0026] In one embodiment of the present invention, in step 5), the thickness of the solid electrolyte coating of the solid-state battery electrode having an ultra-thin solid electrolyte coating is 1.5 um.

[0027] The present invention further provides a solid-state battery pole piece having an ultra-thin solid electrolyte coating prepared based on the above method.

[0028] The present invention further provides the use of a solid-state battery pole piece having an ultra-thin solid electrolyte coating prepared based on the above method in the preparation of a solid-state battery.

[0029] The present invention further provides a solid-state battery, which contains the solid-state battery pole piece with the ultra-thin solid electrolyte coating.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] At present, a key difficulty in applying the technology of coating the surface of electrode sheets with solid electrolytes is how to make the surface of the electrode sheet thin and dense. The present invention provides a method for ultra-thin coating on the surface of solid-state battery electrode sheets, which not only retains the safety of the solid electrolyte coating layer, but also eliminates the negative impact of the solid electrolyte coating layer on the electrochemical performance of the lithium battery, and even improves the rate performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 :Apply solid electrolyte ultra-thin coating technology to the actual picture of the electrode;

[0033] Figure 2 : Example 1 Ultra-thin solid electrolyte surface coated electrode buckle first cycle performance and rate performance;

[0034] Figure 3 : Comparative Example 1: The first cycle performance and rate performance of the electrode plate coated with the ultra-thin solid electrolyte surface;

[0035] Figure 4 : The first cycle performance and rate performance of the thin solid electrolyte surface coated electrode of Examples 2, 3, 4, and 5. DETAILED DESCRIPTION

[0036] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] Example 1

[0038] Prepare a solid electrolyte slurry with a solid content of 15wt%, and the solid electrolyte uses LATP (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ), the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing, the linear speed of the stirrer is 4m / s, and the stirring is carried out for 2h. Then the prepared solid electrolyte slurry is refined by a sand mill, the feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 100nm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry, and the ratio of PVDF to solid electrolyte is 13:87, and then a disperser is used for stirring, the stirring linear speed is 4m / s, and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and a three-stage oven with a length of 7m is used for baking, the walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95,105,100℃. Obtain an ultra-thin solid electrolyte surface coated pole piece.

[0039] Example 2

[0040] Prepare a solid electrolyte slurry with a solid content of 15wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring time is 2h. The prepared solid electrolyte slurry is then refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 100nm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry, and the ratio of PVDF to solid electrolyte is 13:87. Then a disperser is used for stirring, and the stirring linear speed is 4m / s, and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and a three-stage oven with a length of 7m is used for baking. The walking speed is 15mm / s, the micro-concave mesh number is 150 mesh, and the oven temperature is 95, 105, 100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0041] Example 3

[0042] Prepare a solid electrolyte slurry with a solid content of 15wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring time is 2h. Then the prepared solid electrolyte slurry is refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 4h, a solid electrolyte slurry of about 800nm ​​is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry. The ratio of PVDF to solid electrolyte is 13:87, and then a disperser is used for stirring. The stirring linear speed is 4m / s and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and baked in a three-stage oven with a length of 7m. The walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95, 105, 100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0043] Example 4

[0044] Prepare a solid electrolyte slurry with a solid content of 30wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring is carried out for 2h. The prepared solid electrolyte slurry is then refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 400nm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry, and the ratio of PVDF to solid electrolyte is 13:87. Then a disperser is used for stirring, and the stirring linear speed is 4m / s, and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and a three-stage oven with a length of 7m is used for baking. The walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95,105,100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0045] Example 5

[0046] Prepare a solid electrolyte slurry with a solid content of 15wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring time is 2h. The prepared solid electrolyte slurry is then refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 100nm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry, and the ratio of PVDF to solid electrolyte is 25:75. Then a disperser is used for stirring, and the stirring linear speed is 4m / s, and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and a three-stage oven with a length of 7m is used for baking. The walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95, 105, 100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0047] Comparative Example 1

[0048] Alumina slurry with a solid content of 15wt% was prepared. The solvent was NMP and 0.2wt% of the dispersant PVP was added. A stirrer was used for stirring and dispersing. The linear speed of the stirrer was 4m / s and the stirring time was 2h. The prepared alumina slurry was then refined by a sand mill. The feed rate of the sand mill was 5L / min, the linear speed was 50m / min, the filling rate of the grinding medium was 48%, and the grinding medium used was zirconium oxide beads. After sand milling for 6h, an alumina slurry of about 100um was obtained. A certain amount of PVDF was added to the refined alumina slurry. The ratio of PVDF to alumina was 13:87, and then a disperser was used for stirring. The stirring linear speed was 4m / s and the stirring time was 6h. The prepared alumina slurry was coated on the surface of the battery pole piece using a micro-concave coater and baked in a three-stage oven with a length of 7m. The walking speed was 15mm / s, the micro-concave mesh number was 250 mesh, and the oven temperature was 95, 105, 100℃. An ultra-thin alumina surface coated pole piece is obtained.

[0049] Comparative Example 2

[0050] Prepare a solid electrolyte slurry with a solid content of 50wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring time is 2h. Then the prepared solid electrolyte slurry is refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 1.5μm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry. The ratio of PVDF to solid electrolyte is 13:87, and then a disperser is used for stirring. The stirring linear speed is 4m / s and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and baked in a three-stage oven with a length of 7m. The walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95, 105, 100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0051] Comparative Example 3

[0052] Prepare a solid electrolyte slurry with a solid content of 15wt%, solid electrolyte Li 1.3 Al 0.3 Ti 1.7(PO4)3, the solvent is NMP and 0.2wt% of the dispersant PVP is added, and a stirrer is used for stirring and dispersing. The linear speed of the stirrer is 4m / s, and the stirring time is 2h. Then the prepared solid electrolyte slurry is refined by a sand mill. The feed rate of the sand mill is 5L / min, the linear speed is 50m / min, the filling rate of the grinding medium is 48%, and the grinding medium used is zirconium oxide beads. After sand milling for 6h, a solid electrolyte slurry of about 100nm is obtained. A certain amount of PVDF is added to the refined solid electrolyte slurry. The ratio of PVDF to solid electrolyte is 5:95, and then a disperser is used for stirring. The stirring linear speed is 4m / s and the stirring time is 6h. The prepared solid electrolyte slurry is coated on the surface of the battery pole piece using a micro-concave coater, and a three-stage oven with a length of 7m is used for baking. The walking speed is 15mm / s, the micro-concave mesh number is 250 mesh, and the oven temperature is 95, 105, 100℃. An ultra-thin solid electrolyte surface coated electrode is obtained.

[0053] The coating thickness, peeling force and first effect of the electrode sheets obtained in the above embodiments and comparative examples are shown in Table 1.

[0054] Among them, the coating thickness test method is: use a screw micrometer to test the thickness of the coated electrode and the thickness of the uncoated electrode, and the difference between the two is the coating thickness.

[0055] Peel force test method: Fold the adhesive surface of one end of a 300mm long tape sample into a laminate of about 12mm long, hold the laminate, and naturally stick the other end of the sample to the surface of the steel plate without any pressure, and roll the sample back and forth twice with a roller (rolling speed 10±0.5mm / s). No bubbles should be left between the sample and the steel plate. The prepared sample must be tested within 1 minute. Peel off the overlapping end of the folded adhesive tape from the plate by about 25mm, fix the plate in the fixture of the tensile tester, clamp the free end of the adhesive tape in another fixture, peel it at a speed of 5.0±0.2m / s, and record the peel force.

[0056] First efficiency test: Assemble and charge the battery, use metallic lithium for the negative electrode and the prepared electrode for the positive electrode, and test the ratio of the first discharge cycle to the first charge cycle capacity.

[0057] Table 1 Coating thickness, peeling force, and initial effect of the electrode sheets obtained in each embodiment and comparative example

[0058]

[0059] It can be seen from Table 1 that the thinner the coating thickness, the higher the first efficiency of the battery; the higher the peeling force (that is, the higher the PVDF content), the lower the first efficiency; using solid electrolyte coatings, such as LATP and LLZTO, the first efficiency is higher than that of alumina coatings.

[0060] The actual picture of the pole piece of Example 1 using the solid electrolyte ultra-thin coating technology is as follows Figure 1 As shown,

[0061] The first cycle performance and rate performance of the electrode plate coated with the ultra-thin solid electrolyte obtained in Example 1 are as follows Figure 2 shown. Figure 2 The method for obtaining the results is as follows: assemble a buckle battery using ultra-thin LLZTO coated electrodes and uncoated electrodes respectively, and test the first efficiency of the buckle battery and the rate performance of 0.1C-0.2C-0.5C-1C-2C-3C-5C-0.1C.

[0062] from Figure 2 It can be seen that the ultra-thin LLZTO coating has no negative impact on the discharge capacity and first efficiency of the battery, while also improving the rate performance of the battery.

[0063] Comparative Example 1: The first cycle performance and rate performance of the electrode plate coated with the ultra-thin solid electrolyte surface are as follows Figure 3 As shown, Figure 3 The method for obtaining the results is as follows: use ultra-thin LLZTO coated electrodes and ultra-thin alumina coated electrodes to assemble a buckle battery, respectively, and test the first efficiency of the buckle battery and the rate performance of 0.1C-0.2C-0.5C-1C-2C-3C-5C-0.1C.

[0064] from Figure 3 It can be seen that the ultra-thin LLZTO coating has no effect on the discharge capacity of the battery, and its first efficiency and rate performance are better than those of the ultra-thin alumina coating.

[0065] The first cycle performance and rate performance of the electrode plate coated with thin solid electrolyte on the surface of Examples 2, 3, 4, and 5 are as follows Figure 4 As shown, Figure 4 The method for obtaining the invention is as follows: assemble a buckle battery using the electrodes obtained in Examples 2, 3, 4, and 5 respectively, and test the first efficiency of the buckle battery and the rate performance of 0.1C-0.2C-0.5C-1C-2C-3C-5C-0.1C.

[0066] from Figure 4 It can be seen that the 1.5um ultra-thin LLZTO coating has the best first effect and rate performance compared with other materials and thickness coatings.

[0067] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating, characterized in that: The steps include:. 1) preparing a solid electrolyte slurry; 2) refining the dispersed solid electrolyte slurry with a sand mill to obtain a refined solid electrolyte slurry with particles of less than 200 nm; 3) adding the refined solid electrolyte slurry to the binder PVDF and stirring; 4) applying the solid electrolyte slurry prepared in step 3) on the surface of the electrode using a micro-concave coating machine, and drying to obtain a battery electrode with a surface coated with a solid electrolyte; 5) The battery pole piece with the solid electrolyte coated on the surface is subjected to a heating and rolling process to obtain a solid-state battery pole piece with an ultra-thin solid electrolyte coating.

2. The method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating according to claim 1, characterized in that: The solid content of the solid electrolyte slurry in step 1) is 5 to 40 wt %; The solid electrolyte material of the solid electrolyte slurry in step 1) is an oxide solid electrolyte, a sulfide solid electrolyte or a halide solid electrolyte, selected from one or a combination of LATP, LLZO, LLZTO, LLTO, LAGP, LSPC, LGPS, LIC or LYC; The solvent of the solid electrolyte slurry in step 1) is selected from N-methyl-2-pyrrolidone; The solid electrolyte slurry of step 1) is added with a dispersant, the amount of which is 0.1 wt% to 1 wt%; the dispersant is selected from one or a combination of polyvinyl pyrrolidone, herring oil or PAM; When preparing the solid electrolyte slurry in step 1), the solid electrolyte material, solvent and dispersant are stirred and dispersed using a stirrer, and the linear speed of stirring the solid electrolyte slurry is 1 to 6 m / s.

3. The method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating according to claim 2, characterized in that: The solid content of the solid electrolyte slurry in step 1) is 15wt%; The solid electrolyte material of the solid electrolyte slurry in step 1) is LATP; A dispersant is added to the solid electrolyte slurry in step 1), the amount of the dispersant added is 0.2wt%, and the dispersant is selected from polyvinyl pyrrolidone; The linear speed of the stirring and dispersion using the stirrer was 4 m / s.

4. The method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating according to claim 1, characterized in that: In step 2), the feed rate of the sand mill is controlled at 1-30 L / min, the linear speed of the sand mill is controlled at 20-90 m / min, the filling rate of the sand mill is controlled at 25-65%, and the grinding media used in the sand mill is selected from one or a combination of zirconium oxide beads, glass beads, steel beads or zirconium silicate beads.

5. The method for preparing a solid-state battery electrode sheet having an ultra-thin solid electrolyte coating according to claim 1, characterized in that: In step 3), the mass ratio of PVDF to solid electrolyte is 6:94 to 25:75; in step 3), a disperser is used for stirring, the stirring line speed of the disperser is 1 to 6 m / s, and the stirring time of the disperser is 1 to 12 h.

6. The method for preparing a solid-state battery electrode having an ultra-thin solid electrolyte coating according to claim 1, characterized in that: In step 4), the coating speed of the micro-dimpled coater is 5 to 60 mm / s, and the number of micro-dimpled meshes is 50 to 300 meshes; In step 4), drying is performed in an oven at a temperature of 90 to 120°C.

7. The method for preparing a solid-state battery electrode sheet having an ultra-thin solid electrolyte coating according to claim 1, characterized in that: In step 5), when the heating roller pressing process is performed, the pressure of the roller press is 10 to 80 tons, and the temperature of the heating roller is 60 to 110° C.; In step 5), the thickness of the solid electrolyte coating of the solid-state battery electrode having an ultra-thin solid electrolyte coating is 1.5 um.

8. A solid-state battery electrode having an ultra-thin solid electrolyte coating obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the solid-state battery electrode having an ultra-thin solid electrolyte coating as claimed in claim 8 in the preparation of a solid-state battery.

10. A solid-state battery, characterized in that: A solid-state battery electrode having an ultra-thin solid electrolyte coating as claimed in claim 8.